Deux ex Machina (“ God From the Machine”): Exploring Digital Worship in the Salvation Ministries, Port Harcourt, Nigeria - Christopher Onyewuchi Opara; Ndidi Justice Gbule; Rowland Olumati (Asosiasi Khazanah Cendekia, 2023)
This paper presents a sociological exploration of the digital worship practices of the Salvation Ministries in Port Harcourt. It investigates the impact of technology on the members’ and how it engages their relationship with the Divine. Utilizing qualitative research, including interviews with members and analysis of online reviews, the study examines the role of digital worship in fostering relationships between members and the divine. It employs the Media and Technological Determinism theories to examine this relationship in depth. The paper also examines the implications of the emergence of the “God from Machine” in worship services, arguing that worshippers are constructing a new type of connection that transforms their religious experiences. The findings demonstrate that digital worship has significantly expanded the reach of Salvation Ministries beyond its physical boundaries. Virtual sermons and prayer sessions have strengthened the sense of community among members, facilitating easier connections with leaders and fellow worshippers. However, caution is advised regarding the potential risks of excessive reliance on technology, diminished personal interaction, and substituting genuine spiritual experiences. In conclusion, the paper emphasizes the importance of balancing embracing technology and preserving the authenticity and sincerity of spiritual practices.